Barker-like systems of sequences and their processing - Holubnychyi, A.G. (Технология и конструирование в электронной аппаратуре, 2013)
New systems of binary sequences, that give the similar correlation properties after signal processing as that of the Barker sequences, are suggested and analyzed. The author considers processing of such systems, as well as ways of their application to radio systems and their comparison with complementary sequences. Предложены и проанализированы новые системы бинарных последовательностей, которые дают такие же свойства функции автокорреляции после обработки сигналов, что и последовательности Баркера. Рассмотрены принцип их обработки, пути использования в радиосистемах, выполнен их сравнительный анализ с комплементарными последовательностями. Запропоновано та проаналізовано нові системи бінарних послідовностей, які дають такі ж властивості функції автокореляції після обробки сигналів, що і послідовності Баркера. Розглянуто принцип їх обробки, шляхи використання в радіосистемах, виконано їх порівняльний аналіз з комплементарними послідовностями.